GIS as an essential component of the Integrated Information System for District Heating Companie - Gębski, Wojciech; Niemyjski, Olgierd (Instal, 2023)
Geographic Information Systems – GIS has been implemented in District Heating Companies for many years. It is now a standard tool for collecting and storing technical data for the District Heating System (DHS) in many companies in Poland. The article presents an overview of GIS systems that have found application in District Heating Companies. The basic functionalities and data analysis modules, which have been integrated into one coherent system called Integrated Information System – IIS, are discussed. The advantages of using such a system and its application as a tool to support the processes of optimizing the operation of a District Heating Network in technical and economic terms are presented. Additional functionality of the system is cooperation with specialized programs used for specific tasks in the district heating industry. The cooperation with a calculation program used in District Heating Companies for the purpose of simulating the operation of a District Heating Network for given conditions of heat demand is presented.